The following are the steps:
1. First, we need to define symbols and their meanings.
2. Then we obtain an expression for average drift velocity of electrons in terms of resistivity (electric field) and current density.
v = a t = e E τ /m = e J ρ τ / m ---
3. Then we obtain an expression for average drift velocity in terms of current (charge flowing) across any cross section.
v = J / (n e)
4. Equate them both. we get the answer.
Relaxation time = average time between two successive collisions of an electron = τ
emf applied across a resistor/conductor = V
Resistance of the conductor = R = ρ L / A
Resistivity = ρ
conductivity = s = 1/r
Area of cross section of the resistance = A
Length of the resistance wire = L
mass of an electron = m
electrostatic charge on an electron = e
drift velocity of an electron = v
current flowing in the conductor = I = V /R
N = Avogadro number
f = number of free conducting electrons (in the outermost shell) in one atom
d = density of the conductor
M = molar mass of the conductor
n = electron volume density = number of electrons in unit volume of a conductor
total number of electrons = Mass * N * f /Molar mass = A L d N f / M
n = number / volume = d N f / M
Electric field intensity = E = V / L, assuming that it is uniform along the length of the conductor wire.
Force on an electron in this electric field = F = e E
Acceleration = F / m = a = e E /m = e V / (m L)
current density = J = I / A = V / (A R) = V A / ( r A L) = V /(r L)
J = σ E = E / ρ
Or, E = J ρ
Velocity gained in between collisions due to electric field E and force F = v
v = v_i + a τ = 0 + e E τ /m = e J ρ τ / m --- (1)
The average of velocities v_i of all electrons just after collisions is 0, as they get bounced in all random directions. Hence the average velocity of an electron along the length of a resistor or conductor wire is equal to that gained due to electrostatic field E.
So drift velocity = v = e J ρ τ / m --- (2).
I = charge crossing a cross section in time t / time t
So, I = e (n A v t) / t = n e A v
J = n e v
Substituting in (2) we get,
J / (n e) = v = e J ρ τ / m
=> τ = m / ne² ρ
Or, ρ = m / (n e² τ)